PENGELOLAAN TANAH LABA PURA LUHUR PAKENDUNGAN UNTUK PEMBANGUNAN AKOMODASI DI BIDANG KEPARIWISATAAN DI KABUPATEN TABANAN - I Gusti Bagus Agung Kusuma Atmaja (Jurnal AKSES, 2019)
Land possesion temple at Tabanan Regency generally used for support the ceremony needs from the temple and the other, even now used can joined for tourism accomodation building. The problems would be observed those were: first, how does the use of Tanah Laba Pura to build the accomodation for the tourism industry; and second, how does the benefit of investing Tanah Laba Pura for the accomodation in tourism industry of economy and religious communal perspective. The method was used in this research was the empirical laws research with legislation, case, conceptual and sociology laws, by using the primary and secondary data sources and the location of this research was in Pura Luhur Pakendungan, Beraban village, Kediri, Tabanan, Bali. This research used four technics in compiling data those were interview, observation, documentation and noted with interpretation analysis. The result of this research showed that nine plot of land possesion temple were used for rice field, farming and pasraman, a plot of that land was used for tourism accommodation that was managed by investor.